Hair cycle and dermic follicular volume of the wild rodent, agouti (Dasyprocta prymnolopha), raised in captivity, in the northeast region of Brazil - F.L. Silva; A.G.S. Nascimento; R.L.S. Silva; H.J. Rocha Neto; J.L.R. Sarmento; N.M.S.R. Amorim; D.O. Bezerra; H.M.A. Monteiro; M.A.M. Carvalho; M.F. Cavalcanti Filho; N.M. Argôlo Neto (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The objective of this analysis was to evaluate the hair cycle for one year and to compare the dermal follicular volume of the interscapular, lateral and femoral middle abdominal regions of males and females bred in captivity in the city of Teresina-PI. The practices of this experiment were approved by CEUA (589/19) and SISBIO (70275-2). Six agoutis (three males and three females) were used, hair samples for the trichogram were collected every 30 days, from the beginning of October 2019 to September 2020. The hairs were extracted from the three regions with the hemostatic forceps, and then 100 hairs from each region were glued to a microscopy slide. The climatic data from the city of Teresina- PI were obtained from embrapa's meteorological bulletin. To determine dermal follicular volume, analyses of histological sections were performed using the software and image J. Variance analysis (ANOVA) was performed, followed by the Tukey test at 5% probability. The number of telogen hair was higher than the anagen hair during the study no matter the dry season (males 98.8% and females 98.9 %) or rainy (males 96.8% and females 98.3%). There were no follicular stereological variations between the sexes.